DAMPAK AKTIVITAS PELABUHAN CONTAINER TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT NELAYAN DI KELURAHAN BUNGKUTOKO KECAMATAN NAMBO KOTA KENDARI - Sukmawati Abdullah; Rosmawaty Rosmawaty; Anita Beatrix (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to find out the impact of container port activities on the SocioEconomic Condition of The Fishing Community in Bungkutoko Village, Nambo District, Kendari City. This research was conducted in August to October 2020, in Bungkutoko Village, Nambo District of Kendari City.. The research method uses descriptive qualitative. The results of this study showed that the impact of container port activities on socioeconomic conditions in the fishing community in Bungkutoko Village has a positive impact on the community in Bungkutoko Village where the community has job opportunities by working as a Loading and Unloading Worker (TKBM) at container port. The existence of Container port not only opens job opportunities in the port but also able to create business opportunities for the people around the port area. So that the income level of people in Bungkutoko village becomes better. but member negative impact on the economy of fishermen around the port because the area where fish and install rajungan is now not as wide as before the existence of the port so it affects the income for the fishermen.